ACADEMIC SUPERVISION AND PEDAGOGICAL COMPETENCY AS DETERMINANTS OF TEACHER PERFORMANCE - Sehan Rifky; Farihin (Adisam Publisher, 2024)
Teacher performance is related to the quality, quantity of output and reliability that teachers have in carrying out their duties. Teachers who have high performance can improve the quality of education. Teacher performance is one of the main factors that determines the success of the educational process in schools. Assessment of teacher performance in managing the learning process as a process of providing estimates of the quality of teacher performance in managing the learning process, is an integral part of a series of academic supervision activities. If it is said that academic supervision is a series of activities to help teachers develop their abilities, then in its implementation it is necessary to first carry out an assessment of the teacher's abilities, so that aspects that need to be developed and how to develop them can be determined. The performance produced by teachers cannot be separated from the contribution of academic supervision carried out by the school principal and the pedagogical competence they possess. This indicates that the implementation of academic supervision and pedagogical competence is getting better.